PERENCANAAN KOMUNIKASI INDONESIAN YOUTH EDUCATE AND SOCIAL DALAM MENGIMPLEMENTASIKAN PROGRAM I-YES MENGAJAR - Anggeh Afelina Hutagaol; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Quality education in Indonesia is still not evenly felt throughout the country including remote areas in Riau province. Even though in order to create a uniform acceleration of development, especially in the field of education, participation from all parties is needed. Not only relying on the central government, but also the activeness of the provincial government, local government and cross-community, especially the youth. This is the background of Indonesian Youth Educate and Social (I-YES) to create a 3T regional education program (Frontier, Outermost, Disadvantaged), namely I-YES Mengajar.The purpose of this study is to look at the planning of communication audiences, channel planning and communication media, message planning and communication planning evaluation by I-YES in implementing the I-YES Mengajar program.This research uses descriptive qualitative research type. The subject of this study consisted of six persons, where the informants were directly involved in the I-YES Mengajar program. Subjects were selected using a purposive technique. This study uses data collection techniques through semistructural interviews, observation, and documentation. To achieve the validity of the data in this study the authors used an extension of participation and triangulation.The results of the study show that firstly, the target audience in the I-YES Mengajar program consists of four target groups namely the main target is the target of volunteers namely youth in Pekanbaru city, then the government's target, the target of funders and the target community I-YES Mengajar. Second, the dominant media used in message delivery is instagram social media and is supported by channels and other communication media. Third, the message conveyed in the I-YES Mengajar program is a form of verbal and nonverbal messages as well as messages that are informative, persuasive and educative and supported by data, photos and videos about the actual conditions experienced by children in the 3T area. Fourth, I-YES evaluation is carried out in two stages. The first evaluation is an internal evaluation and the second evaluation is an external evaluation.Key Words: Communication Planning, Model of Assifi dan French, Non-Goverment Organizations.